Proceedings of the International Conference on Research and Academic Community Services (ICRACOS 2019) 2020
DOI: 10.2991/icracos-19.2020.1
|View full text |Cite
|
Sign up to set email alerts
|

Digital Workplace Implementation To Promote Gender Equality

Abstract: The focus of this research is to provide an explanation of how the digital workplace can help to promote gender equality in the organization. We conduct interviews with 4 managers and 8 selected woman on different organization regarding expected condition at the workplace. In the Organization perspective, Interviews revealed Regulation and Financial problem is the most important things before implementing digital workplace while for the employees adequate training is needed. This paper provides an explanation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…A digital workplace encompasses a variety of technologies and practices that improve employees' digital work experience, regardless of their physical location, surpassing traditional concepts of information and communication technologies (Marsh, Vallejos, and Spence,2022). As stated by Dery, Sebastian, and Van Der Meulen (2017), a digital workplace refers to an integrated digital environment where various tools are utilised, ranging from enterprise resource planning software to social intranets (Nitschke et al 2020), employee portals, and email systems (Zimmer, Baiyere, and Salmela, 2020), virtual meeting tools (Herrera et al 2012), dashboards, feeds, alerts, and calendars (Attaran et al 2019). According to Hamburg (2020), the digital workplace encompasses all the digital technologies and services utilised by individuals in their current work environment, including both existing and forthcoming ones.…”
Section: Digital Workplacementioning
confidence: 99%
See 1 more Smart Citation
“…A digital workplace encompasses a variety of technologies and practices that improve employees' digital work experience, regardless of their physical location, surpassing traditional concepts of information and communication technologies (Marsh, Vallejos, and Spence,2022). As stated by Dery, Sebastian, and Van Der Meulen (2017), a digital workplace refers to an integrated digital environment where various tools are utilised, ranging from enterprise resource planning software to social intranets (Nitschke et al 2020), employee portals, and email systems (Zimmer, Baiyere, and Salmela, 2020), virtual meeting tools (Herrera et al 2012), dashboards, feeds, alerts, and calendars (Attaran et al 2019). According to Hamburg (2020), the digital workplace encompasses all the digital technologies and services utilised by individuals in their current work environment, including both existing and forthcoming ones.…”
Section: Digital Workplacementioning
confidence: 99%
“…Organisational activities also entail risks and necessitate protection. In understanding digital workplace implementation to promote gender equality, in a study conducted by Yalina (2019), interviews were conducted with four managers and eight women from different organisations to gain insights into workplace expectations. The interviews revealed that, from an organisational standpoint, the crucial factors to consider before implementing a digital workplace are management and financial issues, as well as the necessity for comprehensive employee training which is sometimes lacking in organisations.…”
Section: Constraints Of Digital Workplace Implementationmentioning
confidence: 99%
“…and society. Unforeseen circumstances can complicate the process of digitalization and introduce novel obstacles along the path towards digital transformation (Yalina, 2020). The primary hurdle in digitalization does not solely revolve around technology.…”
Section: Introduce the Problemmentioning
confidence: 99%